Case report: Multiple brain intravascular papillary endothelial hyperplasia: incidence, diagnostic challenges, and management approach - Anghileri, Elena; Pollo, Bianca; Ferroli, Paolo; Aquino, Domenico; Demichelis, Greta; Schiariti, Marco; Ferrau, Francesco; Chiapparini, Luisa; Cuccarini, Valeria (Frontiers in Neurology, 2023)
Multiple hemorrhagic brain lesions are mainly diagnosed based on clinico-radiological features integrated with histological data. Intravascular papillary endothelial hyperplasia (IPEH), or Masson's tumor, is a very rare entity, particularly when localized in the brain. In this study, we describe a case of multiple recurrent brain IPEHs and provide details on the diagnostic phase, therapeutic approaches, and related challenges. A 55-year-old woman presented with a relapsing neurological deficit. Brain magnetic resonance imaging (MRI) revealed a hemorrhagic right frontal-parietal lesion. When new neurological symptoms occurred, subsequent MRI scans detected more bleeding cerebral lesions. She underwent a series of single hemorrhagic lesion debulking. For any samples that underwent histopathological examination, the first results were not informative; the second and the third results revealed hemangioendothelioma (HE); and the fourth results led to the IPEH diagnosis. Interferon alpha (IFN-α) and subsequently sirolimus were prescribed. Both were well tolerated. Clinical and radiological features remained stable 43 months after starting sirolimus therapy and 132 months after the first diagnosis. To date, 45 cases of intracranial IPEH have been reported, mostly as single lesions without parenchymal location. They are usually treated by surgery and sometimes by radiotherapy upon recurrence. Our case is notable for two main reasons: because of the consecutive recurrent multifocal exclusively cerebral lesions and the therapeutic approach we used. Based on multifocal brain recurrence and good performance, we propose pharmacological therapy, including IFN-α and sirolimus, to stabilize IPEH.